2009
DOI: 10.1038/ejcn.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum 25(OH)D concentration in women of childbearing age and their preschool children in Northern Jordan during summer

Abstract: Objective: To assess vitamin D status in women and their children aged 4-5 years in Northern Jordan during summer. Design: A cross-sectional study in which 93 mother-child dyads volunteered through local community centers between June and July 2007. Anthropometric measurements were performed and information on socioeconomic status, health issues, lifestyle factors and nutritional intake were obtained from mothers through a questionnaire. Main measures: Serum 25(OH)D and serum parathyroid hormone (PTH) levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 34 publications
3
36
1
Order By: Relevance
“…As for gender, most studies have reported that women had lower levels of vitamin D compared to men due to high body fat composition and the effect of childbearing [29]. Our results did not support such a claim—both men and women exhibited similar rates of vitamin D deficiency.…”
Section: Discussioncontrasting
confidence: 86%
“…As for gender, most studies have reported that women had lower levels of vitamin D compared to men due to high body fat composition and the effect of childbearing [29]. Our results did not support such a claim—both men and women exhibited similar rates of vitamin D deficiency.…”
Section: Discussioncontrasting
confidence: 86%
“…Although there is evidence for an inverse relation between 25(OH)D and serum PTH in older children and adolescents, estimates of 25(OH)D required for maximal suppression of PTH vary from 30 to 100 nmol/L (4,12,13,15,18,32). In our study, a serum 25(OH)D concentration of '61 nmol/L was needed to minimize PTH concentrations.…”
Section: Discussionmentioning
confidence: 68%
“…Studies assessing the association of serum 25(OH)D and PTH concentrations have been largely based on older children and adults (4,5,(12)(13)(14)(15)(16)(17)(18)(19). Little information is available about whether a plateau in PTH concentration is also evident in young children.…”
Section: Introductionmentioning
confidence: 98%
“…Prior research has emphasized that it is vital that individuals allow themselves sufficient exposure to sunlight to avoid vitamin D deficiency 37. On average, 5 to 10 minutes of direct exposure of limbs to sunlight (half the minimal erythema dose) produces approximately 3000 IU of vitamin D 3 3; however, the surface area of a person’s body exposed to direct sunlight depends on their choice of clothing, deployment of sunscreen, and general lifestyle 38. The high prevalence of vitamin D deficiency among Middle Eastern women has previously been associated with inadequate exposure of their skin to sunlight because of their countries’ conservative clothing customs, which specify that when outside they should wear items (eg, niqab, hijab) that cover most of their bodies 12,16,18.…”
Section: Discussionmentioning
confidence: 99%